1985
DOI: 10.1055/s-2007-1014071
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal Resection - State of the Art

Abstract: Sleeve resection of the trachea and reconstruction by end-to-end anastomosis is seen as the method of choice in the treatment of short and long stenoses of the trachea following long-term artificial respiration and tumors. The experience with tracheal resection in 73 patients operated upon at 2 different thoracic units is analyzed. Postintubation was the main indication for operation in 63% of the patient population. The 30-day postoperative mortality rate was 8% with a total mortality of 19%. A satisfactory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 3 publications
0
14
0
2
Order By: Relevance
“…[27] The definitive treatment of benign tracheal stenosis remains tracheal reconstruction surgery. [28] However, surgery could not be performed in our patients both because of lack of surgical expertise and unwillingness of the patients. Five rigid bronchoscopy procedures were performed for foreign body removal of which four were successful.…”
Section: Discussionmentioning
confidence: 99%
“…[27] The definitive treatment of benign tracheal stenosis remains tracheal reconstruction surgery. [28] However, surgery could not be performed in our patients both because of lack of surgical expertise and unwillingness of the patients. Five rigid bronchoscopy procedures were performed for foreign body removal of which four were successful.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] In this series, seven patients with tracheal and tracheosubglottic stenotic lesions were resected with no mortality; an improvement over the results of Arola et al and Maassen et al, who reported mortality rates of 18% and 19% consequently. 17,18 Postoperatively, two complications were noted: ventilation for three weeks in one patient, and moderate anastomotic restenosis in the other. Excessive anastomotic tension is without doubt the single most important cause of failure in tracheal surgery.…”
Section: Discussionmentioning
confidence: 97%
“…The more permanent treatment is still open surgery such as end-toend anastomosis. Unfortunately the procedure is more suitable for defect less then 6 cm in length and the longer the segment it will create tension and granulation tissue formation [1][2][3]. However, for defects larger then the above measurement, reconstruction by grafts, slide tracheoplasty and prostheses need to be used.…”
Section: Introductionmentioning
confidence: 99%